Edukasi Publik dalam Lomba Desain Poster Simbolik: Studi Kasus Lomba Poster Simbolik Tentang Pencegahan dan Penanganan Kekerasan Seksual - Armayuda, Erik (Bina Nusantara University, 2024)
Sexual violence in educational settings deprives students of the freedom to develop their potential in a healthy, safe, and optimal environment. Various forms of sexual violence harm students, educators, and staff, potentially hindering or eliminating their opportunities to learn and teach. In alignment with Sustainable Development Goal 16: Peace, Justice, and Strong Institutions, the Ministry of Education, Culture, Research, and Technology issued Regulation No. 30 of 2021 for higher education institutions. Initiatives under the Prevention and Handling of Sexual Violence (PPKS) program have shown promising results. One example is the Symbolic Poster Design Competition as Public Education, where 391 participants showed great enthusiasm. The research aimed to describe the competition process and raise awareness about the importance of PPKS. The competition was organized using Erick Karjaluoto's design method. This paper focuses on two main discussions: how to design criteria and schemes for a competition that educates the younger generation, and the participants' responses to the competition. The study concluded that the symbolic poster competition encouraged participants to show sympathy towards victims, avoiding traumatic elements in their designs. While solution-oriented posters are useful for potential users, designs with constructive purposes are meaningful for organizers, users, and designers. Keywords: Poster Design Competition, Design Method, Symbolic Poster, Design Competition Mechanism, SDG Goal 16 Kekerasan seksual dalam konteks pendidikan merampas kebebasan siswa untuk mengembangkan potensi mereka dengan kondisi yang sehat, aman, nyaman, dan optimal. Berbagai bentuk kekerasan seksual mengakibatkan kerugian bagi mahasiswa dan para pendidik serta staf kependidikan, yang dapat menghambat atau bahkan menghilangkan kesempatan mereka untuk belajar dan mengajar. Sebagai perwujudan SDG Goals 17 yaitu Peace, Justice and Strong Institutions, maka dikeluarkannya Peraturan Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi (Permendikbudristek) No. 30 Tahun 2021 di lingkungan perguruan tinggi. Kegiatan dalam rangka PPKS menunjukkan hasilnya. Salah satu contohnya adalah penelitian dengan Lomba Desain Poster Simbolik Sebagai Edukasi Publik. Sebanyak 391 peserta menunjukkkan atusianisme yang besar untuk mengikuti lomba poster simbolik tentang Pencegahan dan Penanganan Kekerasan Seksual (PPKS). Tujuan penelitian ini adalah untuk mendeskripsikan proses kegiatan lomba dan awareness tentang pentingnya PPKS. Metode yang digunakan adalah studi kasus. Permasalahan dalam penelitian ini ada dua yaitu: 1. Bagaimana proses lomba desain dalam mengedukasi para generasi muda? 2. Bagaimana respons peserta lomba? Kesimpulan dari penelitian ini adalah melalui lomba poster simbolik ini mengangkat isu pelecehan seksual dan menaruh simpati kepada korban untuk tidak memberikan unsur traumatis. Desain poster yang solutif akan berguna bagi calon pengguna, namun desain yang memiliki tujuan konstruktif akan bermakna bagi penyelenggara, pengguna, dan desainernya itu sendiri.